Supervision of the Use of Road Project Funds of the Public Works and Spatial Planning Office in Bitung City - Wongkar, Amerlin Lineke; Bogar, Wilson; Kairupan, Sisca B.; Mandagi, Marthinus (Technium Social Sciences Journal, 2025)
The purpose of this study was to determine the supervision of road project funds, especially rehabilitation/maintenance of the Public Works and Spatial Planning Office in Bitung City as well as supporting factors and inhibiting factors. This research uses qualitative descriptive method. The results showed that in the implementation of Road Development, road rehabilitation and maintenance of regional roads which are the responsibility of local governments, especially Bitung City, there are still discrepancies with the applicable provisions in Bitung City. There is a low level of budget realization in the Regional Work Unit (SKPD). This is due to the lack of supervision from the policy holders, either from the executive or the legislature in regional financial management, so that budget control is not effective. In addition, it was also found that the supporting factors in the Role of the Public Works Agency in the Supervision of Bitung City Road Projects are the budget for road project costs and human resources while the inhibiting factors are facilities and infrastructure, insufficient supervision costs, lack of field supervisory personnel and delays in completing road projects.